Influences of the light intensity and the NaCl concentration on the growth of two harmful marine microalgae species Prorocentrum rhathymum and Alexandrium tamarense - Tua, Tran Van; Thanh Xuyen, Dang Thi; Cu, Nguyen Tien; Kim, Dang Dinh (Academia Journal of Biology, 2014)
In Vietnam, among more than 70 harmful marine microalgae species which have been identified [6], Prorocentrum rhathymum and Alexandruim tamarense were two species of Dinophyta that had a very wide distribution on the coastal waters. This study investigated the influences of the light intensity and the NaCl concentration on the growth of these two isolated species in laboratory conditions. The experiment had been carried out in bath cultures in the IMK medium using these two species. The obtained results showed that the light intensity and the NaCl concentration have obviously effects on the growth of these studied species. Both two species prefered low light and their optimum growth required about 2000 - 3000 lux. The NaCl concentration at 20‰ has better effect on the growth of these species in comparison with the other NaCl concentrations at 25‰, 30‰ and 35‰. The conclusion had been affirmed by the analysis of variance (ANOVA) one way of experimental data. The research results have contributed to understand the influences of the environmental factors on the growth of the harmful marine microalgae species.